2021
DOI: 10.1371/journal.ppat.1009825
|View full text |Cite
|
Sign up to set email alerts
|

Increased homeostatic cytokines and stability of HIV-infected memory CD4 T-cells identify individuals with suboptimal CD4 T-cell recovery on-ART

Abstract: Clinical outcomes are inferior for individuals with HIV having suboptimal CD4 T-cell recovery during antiretroviral therapy (ART). We investigated if the levels of infection and the response to homeostatic cytokines of CD4 T-cell subsets contributed to divergent CD4 T-cell recovery and HIV reservoir during ART by studying virologically-suppressed immunologic responders (IR, achieving a CD4 cell count >500 cells/μL on or before two years after ART initiation), and virologically-suppressed suboptimal responde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 84 publications
0
13
0
Order By: Relevance
“…Previous studies had shown the relationship between HIV reservoirs and suboptimal CD4 recovery (55)(56)(57). Interestingly, a recent study showed that the increased homeostatic cytokine levels, especially IL-7 and IL-15, were also associated with HIV reservoirs in T-cell subsets and poor immune reconstitution during cART (58). The role of proinflammatory and homeostatic cytokines in the connection between viral reservoirs recovery and the immunopathogenesis of chronic IA had been reported (59,60).…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies had shown the relationship between HIV reservoirs and suboptimal CD4 recovery (55)(56)(57). Interestingly, a recent study showed that the increased homeostatic cytokine levels, especially IL-7 and IL-15, were also associated with HIV reservoirs in T-cell subsets and poor immune reconstitution during cART (58). The role of proinflammatory and homeostatic cytokines in the connection between viral reservoirs recovery and the immunopathogenesis of chronic IA had been reported (59,60).…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, another study found that in six PWH on ART without detectable viremia, CpG methylation of the HIV 5′ LTR was 20%, 30%, 48%, 71%, 96%, and 100%—compared with < 0.1% in a control group of viremic patients [ 29 ]. These discordant findings suggest that factors such as subtypes of CD4 + T cells [ 30 ], history of infection, duration and type of ART, degrees of turnover of latently infected CD4 + T cells, and inclusion of unintegrated HIV DNA may play a significant role in the variation of DNAm, viral persistence, and latency.…”
Section: Epigenetic Epidemiologic Studies Of Pwhmentioning
confidence: 99%
“…The panel did not reach an agreement about the utility of using inflammation or immune-activation markers in daily clinical practice. In fact, the study of such markers has been proposed by some panelists to further refine decision-making algorithms, with the aim of defining safer and more tailored therapies [32][33][34][35][36][37][38]. However, the clinical relevance of these markers is currently unproven, leading most respondents to express disagreement with their use in clinical practice.…”
Section: Clinical Efficacy: Art-monitoring Strategymentioning
confidence: 99%